Christian Pragmatism an Intellectual Biography of Edward Scribner Ames, 1870-1958. - Peden, W. Creighton (Newcastle upon Tyne : Cambridge Scholars Pub., 2011)
Edward Scribner Ames (1870-1958) was raised in the Midwest as the family moved westward after the Civil War. His father was a minister in the Disciples of Christ, which later was changed to the Christian Church. In between serving several small churches in the Iowa area, the father did various odd jobs. Young Ames joined the Church one Sunday when his father was preaching, and was baptized in the river that afternoon. Ames was able to attend Drake College in Des Moines, Iowa, and did a post-g ...
Keywords: Ames, Edward Scribner, -- 1870-1958.; Theologians -- Biography; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books